Salty sisters: The women of halophiles - Baxter, Bonnie K.; Gunde-Cimerman, Nina; Oren, Aharon (Frontiers in Microbiology, 2014)
A history of halophile research reveals the commitment of scientists to uncovering the secrets of the limits of life, in particular life in high salt concentration and under extreme osmotic pressure. During the last 40 years, halophile scientists have indeed made important contributions to extremophile research, and prior international halophiles congresses have documented both the historical and the current work. During this period of salty discoveries, female scientists, in general, have grown in number worldwide. But those who worked in the field when there were small numbers of women sometimes saw their important contributions overshadowed by their male counterparts. Recent studies suggest that modern female scientists experience gender bias in matters such as conference invitations and even representation among full professors. In the field of halophilic microbiology, what is the impact of gender bias? How has the participation of women changed over time? What do women uniquely contribute to this field? What are factors that impact current female scientists to a greater degree? This essay emphasizes the "herstory" (not “history”) of halophile discovery.